2012
DOI: 10.2174/138161212799958477
|View full text |Cite
|
Sign up to set email alerts
|

G-quadruplex DNA Aptamers and their Ligands: Structure, Function and Application

Abstract: Highly specific and tight-binding nucleic acid aptamers have been selected against a variety of molecular targets for over 20 years. A significant proportion of these oligonucleotides display G-quadruplex structures, particularly for DNA aptamers, that enable molecular recognition of their ligands. G-quadruplex structures couple a common scaffold to varying loop motifs that act in target recognition. Here, we review DNA G-quadruplex aptamers and their ligands from a structural and functional perspective. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
126
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(134 citation statements)
references
References 147 publications
1
126
0
Order By: Relevance
“…Short aptamers that adopt G4 configurations can bind to a wide variety of molecular targets, mainly proteins (such as thrombin, nucleolin, signal transducer and activator of transcription STAT3, human RNase H1, protein tyrosine phosphatase Shp2, VEGF, HIV-1 integrase, HIV-1 reverse transcriptase, HIV-1 reverse transcriptase, HIV-1 nucleocapsid protein, M. tuberculosis polyphosphate kinase 2, sclerostin, insulin, etc. ), but also some other targets (hematoporphyrin IX, hemin, ochratoxin, potassium ions, ATP) [33][34][35]48,49]. Many aptamers recognize specifically different positions on the analyte; for example, TBA recognizes the fibrinogen and heparin binding sites of thrombin.…”
Section: G4 Electrochemical Aptasensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Short aptamers that adopt G4 configurations can bind to a wide variety of molecular targets, mainly proteins (such as thrombin, nucleolin, signal transducer and activator of transcription STAT3, human RNase H1, protein tyrosine phosphatase Shp2, VEGF, HIV-1 integrase, HIV-1 reverse transcriptase, HIV-1 reverse transcriptase, HIV-1 nucleocapsid protein, M. tuberculosis polyphosphate kinase 2, sclerostin, insulin, etc. ), but also some other targets (hematoporphyrin IX, hemin, ochratoxin, potassium ions, ATP) [33][34][35]48,49]. Many aptamers recognize specifically different positions on the analyte; for example, TBA recognizes the fibrinogen and heparin binding sites of thrombin.…”
Section: G4 Electrochemical Aptasensorsmentioning
confidence: 99%
“…Aptamers are a special class of small synthetic oligonucleotides able to form secondary and tertiary structures, larger than small molecule drugs, but smaller than antibodies, with the advantage of being highly specific in binding to small molecules, proteins, nucleic acids and even cells and tissues [33][34][35][36]. The aptamers bind to the targets by a lock and key mode, and the name "aptamer" is from the Latin word aptus, meaning "to fit" [36].…”
Section: Introductionmentioning
confidence: 99%
“…Aptamers have also attracted attention as potential biosensors which could replace more expensive and less stable antibodies (Hianik and Wang 2009;Lv et al 2012;Tucker et al 2012), in addition to acting as receptors for targeted drug delivery. In this second case, polymeric nanoparticles can be modified by aptamers specific to cancer markers which increase the affectivity of drugs which can be transported exclusively to the cancer cells (Farokhzad et al 2004;Lee et al 2011).…”
Section: Target/name Sequence Of Aptamer ( 5´ → 3´) Referencesmentioning
confidence: 99%
“…This approach has been used in the study of the thermodynamic properties of G-quadruplexes (mostly TBA) both in the presence of mono and divalent cations (Mergny et al 1998;Kankia and Marky 2001) and also when nucleotides were substituted in the quadruplex loop (Ohsen et al 2009). The loop part of the G-quadruplex has a considerable influence on the stability and binding properties of aptamers, and several studies have focused on the stability and binding properties of TBA aptamers depending on the substitution of nucleotides in two lateral TT and central TGT loops (see Tucker et al 2012 and references herein). The modification of TGT loops have a substantial effect on the stability and binding properties of TBA aptamers; although substitution in T 3 and T 4 had little effect on TBA properties, the effect on T 12 and T 13 was remarkable (Coppola et al 2008) (see Fig.…”
Section: Structural Polymorphism Of Guanine Quadruplexes and Their Phmentioning
confidence: 99%
“…2,3 It has been shown that thrombin binding aptamer (TBA) and aptamers binding to a number of HIV-1 proteins fold into GQ structures. 4 TBA is probably the most widely known DNA aptamer, as evidenced by a large number of publications related to its biochemical and structural properties. It forms intramolecular GQ with two G-quartets in the core and three loops, one TGT and two TT loops.…”
Section: Introductionmentioning
confidence: 99%